2022
DOI: 10.3389/fmars.2022.839614
|View full text |Cite
|
Sign up to set email alerts
|

Effects of High Salinity Stress on the Survival, Gill Tissue, Enzyme Activity and Free Amino Acid Content in Razor Clam Sinonovacula constricta

Abstract: Salinity can affect the physiological and productive characteristics of bivalves. The razor clam Sinonovacula constricta naturally distributing in intertidal zones and estuarine waters is extensively cultured in China. High-salinity is a serious threat to its culture, especially in pond culture model. Here, we investigated the effects of high-salinity on the survival, gill tissue, enzyme activity and free amino acid content of S. constricta. Individuals were randomly divided into six groups treated with differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…The regulation of organic osmolyte content is an important strategy for the adaptation of organisms to hypotonic and hypertonic conditions because of the low effect on cell physiology [37]. As important organic osmolytes, FAAs have been proven to participate in osmoregulation in many marine mollusks under salinity stress, such as Crassostrea gigas [38], M. lusoria [16], and S. constricta [12]. Likewise, a previous study reported that a freshwater mollusk C. sandai uses FAAs as osmolytes under hyperosmotic conditions [38].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The regulation of organic osmolyte content is an important strategy for the adaptation of organisms to hypotonic and hypertonic conditions because of the low effect on cell physiology [37]. As important organic osmolytes, FAAs have been proven to participate in osmoregulation in many marine mollusks under salinity stress, such as Crassostrea gigas [38], M. lusoria [16], and S. constricta [12]. Likewise, a previous study reported that a freshwater mollusk C. sandai uses FAAs as osmolytes under hyperosmotic conditions [38].…”
Section: Discussionmentioning
confidence: 99%
“…The gill is an important organ responsible for osmoregulation, and its histopathological changes can be used as markers of salinity adaptation [42]. In S. constricta, the salinity (30‰ and 40‰) stress induced the shrinkage of the gill filaments and decreased gill thickness [12]. In S. purpurata, salinity (35‰) stress resulted in shrunken gill filaments and increased filament spacing [13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The distribution of bivalves is determined by hydrodynamic variables, sediment types, and depth of substrates (Whetstone 2005). Sediment features in uence the number and form of clams, whereas salinity in uences the physiological and productive properties of clams (Cao 2022). A total of 306 nos of Villorita cyprinoides shells and 169 nos of Meretrix casta shells were obtained from the ten sample locations of Vembanad estuary.…”
Section: Shell Sizementioning
confidence: 99%
“…Low salinity disrupts the PL osmoregulation, necessitating an increased supply of oxygen. Therefore the high compound which is rich in antioxidant activity is urgently needed (Cao et al, 2022). This increased osmotic pressure disrupts shrimp immune system, rendering them more vulnerable to disease infections (Pang et al, 2019).…”
Section: Introductionmentioning
confidence: 99%